Priest Vladimir Vostokov - Member of the White Movement and Founder of the Brotherhood of the Life-Giving Cross - Biryukova, Yu.A. (The Quarterly Journal of St. Philaret's Institute, 2020)
The article examines the views and activities of the priest Vladimir Vostokov, who played a prominent role in the social and political life of the White South during the Civil war as the leader of the Brotherhood of the Life-Giving Cross organized by him. The author analyzes the reasons for the transformation of the Brotherhood into an Orthodox right-wing nationalist party, as well as the relationship of the priest Vladimir Vostokov with the Church authorities in the South of Russia, the clergy, the Orthodox community, and right-wing political forces. His controversial, but certainly outstanding personality is considered against the background of political processes that took place during this period. For the first time in historiography, this problem is subjected to a comprehensive study and is considered on the basis of sources based on the documentation of a Special meeting of the Volunteer Army, the Provisional Supreme Church administration, the All-Russian National Center, and memoiristics. The author comes to the conclusion that the extremes of the position of the priest Vladimir Vostokov, the idea of a Jew-Masonic conspiracy that he preached, and the desire to include anti-Semitic statements in the official Church discourse at all costs, were perceived negatively. Therefore, the Brotherhood of the Life-Giving Cross created by him did not receive the support of the highest Church authority of the White South. Having been created initially to protect the faith, if necessary even by force of arms, the brotherhood began to acquire the features of a political organization, and was noticed by the right part of the spectrum of political forces. At the same time, Vostokov’s preaching talent, his fervent struggle for faith and love for the Motherland made him a popular preacher among the people. Perhaps this was facilitated by the everyday anti-Semitism of the Cossacks. Of course, the personality of its founder played a decisive role in the fate of the Brotherhood of the Life-Giving Cross.